SIKAP IBU RUMAH TANGGA TERHADAP 10 PROGRAM POKOK PKK DI DESA LUBUK DALAM KECAMATAN LUBUK DALAM KABUPATEN SIAK - Lita Azriani Azriani; Titi Maemunaty Maemunaty; Murni Baheram Baheram (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of thisresearch isthe lack housewife attitude towards 10 program PKK in Desa lubuk Dalam Kecamatan Lubuk Dalam Kabupaten Siak. Formulatiaon of the problem of this study is whether the housewife attitude towards 10 program PKK in Desa Lubuk Dalam Kecamatan Lubuk Dalam Kabupaten Siak classified as positive or negative. The purpose of this study was to determine the housewife attitude towards 10 program PKK in Desa Lubuk Dalam Kecamatan Lubuk Dalam Kabupaten Siak. The population in thisstudy were 55 PKK and the sample 35 PKK with a critical level of 10%, the sample used is random sampling. Instrument collecting data questionnaire with 88 statements and after the trial lived 81 valid statement to be made in the instument of sereach. Data analysis through quantitative descriptive analysis. Presentation of claculation housewife attitude towards 10 program PKK seen from the cognitive component indicators that states could not agree (SS) of 28,34%, agree (S) of 33,60%, less agree (KS) of 25,27%, and disagree (TS) of 13,82%. Presentation of claculation housewife attitude towards 10 program PKK seen from the affective component indicators that states could not agree (SS) of 33,02%, agree (S) of 34,72%, less agree (KS) of 23,28%, and disagree (TS) of 8,99%. Presentation of claculation housewife attitude towards 10 program PKK seen from the conative component indicators that states could not agree (SS) of 32,43%, agree (S) of 39,73%, less agree (KS) of 18,71%, and disagree (TS) of 8,47%. Key words: attitude housewife, 10 program PKK